Population pharmacokinetics of delavirdine and N-delavirdine in HIV-infected individuals. - Smith, Patrick F; Dicenzo, Robert; Forrest, Alan; Shelton, Mark; Friedland, Gerald; Para, Michael; Pollard, Richard; Fischl, Margaret; DiFrancesco, Robin; Morse, Gene D (Clinical pharmacokinetics, 2005)
Delavirdine is a non-nucleoside reverse transcriptase inhibitor used in combination regimens for the treatment of HIV-1 infection. Our objective was to characterise the population pharmacokinetics of delavirdine in HIV-infected patients who participated in the adult AIDS Clinical Trials Group (ACTG) 260 and 261 studies.
Keywords: Adolescent; Adult; Anti-HIV Agents; Body Weight; Carbamazepine; Continental Population Groups; Delavirdine; Double-Blind Method; Drug Therapy, Combination; Female; HIV Infections; Humans; Male; Metabolic Clearance Rate; Middle Aged; Sex Factors